Second‐hit DEPDC5 mutation is limited to dysmorphic neurons in cortical dysplasia type IIA. Issue 7 (17th June 2019) - Lee, Wei Shern; Stephenson, Sarah E. M.; Howell, Katherine B.; Pope, Kate; Gillies, Greta; Wray, Alison; Maixner, Wirginia; Mandelstam, Simone A.; Berkovic, Samuel F.; Scheffer, Ingrid E.; MacGregor, Duncan; Harvey, Anthony Simon; et al.
Abstract: Focal cortical dysplasia (FCD) causes drug‐resistant epilepsy and is associated with pathogenic variants in mTOR pathway genes. How germline variants cause these focal lesions is unclear, however a germline + somatic "2‐hit" model is hypothesized. In a boy with drug‐resistant epilepsy, FCD, and a germline DEPDC5 pathogenic variant, we show that a second‐hit DEPDC5 variant is limited to dysmorphic neurons, and the somatic mutation load correlates with both dysmorphic neuron density and the epileptogenic zone. These findings provide new insights into the molecular and cellular correlates of FCD determining drug‐resistant epilepsy and refine conceptualization of the epileptogenic zone.